Role of Pediatricians in the Ambulatory Care of Children in Taiwan, 1999-2011 - Chieh-Mao Chuang; I-Ching Chan; Yu-Sheng Lee; Pei-Chen Tsao; Chia-Feng Yang; Wen-Jue Soong; Tzeng-Ji Chen; Mei-Jy Jeng (Elsevier, 2015)
Pediatricians are physicians trained to provide comprehensive nonsurgical health care for children, but parents may consult other specialists when seeking medical help for their children. This study was designed to analyze the role of pediatricians and the changes in the patterns of ambulatory visits among different specialties for children under the age of 18 years in Taiwan during the past 13 years. Methods: Data on ambulatory visits of children aged 0-17 years from 1999 to 2011 were retrieved from the National Health Insurance Research Database. The physician's specialty, level of the hospital, year of visit, age of the patient, and diagnoses of each ambulatory visit were analyzed. Four of the most commonly visited specialties-pediatrics, otolaryngology, family medicine, and internal medicine-were compared. The yearly trend of ambulatory visits to different specialties, difference in various age groups, influence of hospital levels, and the top 10 diagnoses were analyzed. Results: A total of 1,618,033 ambulatory visits were identified and enrolled into our study. A comparison of the proportions of ambulatory visits between 1999-2003 and 2007-2011 showed that the proportions of visits increased from 27.1 ± 1.3% to 35.4 ± 1.0% for pediatricians, decreased from 32.8 ± 1.8% to 17.0 ± 0.8% for family physicians, and did not change for otolaryngologists and internal medicine physicians. Specifically, pediatricians were visited more often if the children were younger, or if the health-care facility (level of hospital) was either a medical center or a regional hospital. Upper respiratory tract infection was the top diagnosis, followed by acute bronchitis, and acute and chronic tonsillitis. Conclusions: The role of pediatricians in children's ambulatory care increased in importance from 1999 to 2011 in Taiwan. However, approximately two thirds of children sought ambulatory medical help from nonpediatric physicians. Thus, it is important to educate and encourage parents to visit pediatricians if their children require medical help.